PENINGKATAN LITERASI ETIS PENGGUNAAN GENERATIVE AI PADA MAHASISWA UNIVERSITAS SAHID SURAKARTA - Hardika Khusnuliawati; Dwi Retnoningsih; Astri Charolina (LPPM Universitas Abdurrab, 2026)
The rapid development of Generative Artificial Intelligence (Generative AI) has encouraged its widespread use among students in academic activities. However, the use of Generative AI without adequate ethical literacy may lead to violations of academic integrity and technological dependency. This community service activity aimed to enhance ethical literacy in the use of Generative AI among 53 students of Universitas Sahid Surakarta through a structured socialization program. The implementation employed an educative–participatory approach, including material presentations, reflective discussions, and evaluation through pre-test and post-test instruments based on a Likert scale. The activity resulted in an increase in students’ understanding across all evaluated indicators, ranging from 12% to 18%, particularly in Generative AI conceptual understanding, AI output verification, academic integrity awareness, and ethical AI usage. These findings indicate that the socialization activity was effective in strengthening students’ ethical literacy regarding the use of Generative AI in higher education. The activity is expected to support the reinforcement of academic integrity culture and serve as a foundation for the development of sustainable AI literacy policies and programs within universities.